Semiotic aspects of cinematic discourse - Крисанова, Тетяна Анатоліївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article focuses on the study of semiotic aspects of the cinematic discourse. The sign nature of the cinematic discourse is considered, the interaction of verbal, nonverbal and cinematic semiotic systems aimed at constructing the meaning is determined. The semiotic model of the cinematic discourse is proposed, verbal, nonverbal and cinematic signs of the cinematic discourse which have the features of icons, indices and symbols are distinguished. The semiotic model of the film discourse includes a collective author and collective recipient, a semiotic system, a polycoded utterance, a channel, a mediator – actors, as well as a communicative noise and an inferencial reasoning. The process of the inferencial reasoning is at the heart of the meaning reconstruction by the collective recipient, actualized in the cinematic discourse. Successful meaning reconstruction of the polycoded utterance depends on a common picture of the world and the system of values that exist in the collective consciousness of the author and the recipient. The article highlights the complex relation between the film discourse and the cinematic discourse, whereas the cinematic discourse is considered to comprise the film discourse. The latest includes the process of translating polycoded utterances produced by the collective author. Social and cultural community, a certain historical background predetermine the success of cinematic communication.